2020
DOI: 10.3390/ijerph17103503
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Technology in Pediatric Neurorehabilitation. A Pilot Study of Human Factors in an Italian Pediatric Hospital

Abstract: The introduction of robotic neurorehabilitation among the most recent technologies in pediatrics represents a new opportunity to treat pediatric patients. This study aims at evaluating the response of physiotherapists, patients and their parents to this new technology. The study considered the outcomes of technological innovation in physiotherapists (perception of the workload, satisfaction), as well as that in patients and their parents (quality of life, expectations, satisfaction) by comparing the answers to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…This large cluster covers 19 keywords revolving around promoting a more rounded caretaker/patient dialogue, with a focus on children. Some papers address issues regarding hindered communication with children and how VR can help with that [ 38 , 39 ], as well as the development of communication skills for patients [ 40 , 41 ] and medical staff [ 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This large cluster covers 19 keywords revolving around promoting a more rounded caretaker/patient dialogue, with a focus on children. Some papers address issues regarding hindered communication with children and how VR can help with that [ 38 , 39 ], as well as the development of communication skills for patients [ 40 , 41 ] and medical staff [ 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…After clustering the author keywords, clear distinctions were apparent, with the currently highest trending area of research involving communication and the integration of VR for educational purposes. This topic spans over manifold instances like patient and caretaker interactions, communication training, and new forms of education [ 10 , 38 , 43 ]. The second most prominent field combines telemedicine and VR, with a foray into the development of VR-based “medical professionals.” The focus is on the implementation of a VR setting in which health care professionals do not necessarily need to be physically present, or even involved in the procedure at all [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In general, physiotherapists have been found to have positive attitudes towards the use of robotic technology in rehabilitation, as long as they fulfil their intended goals, are not time consuming to set up, and therapists receive adequate training in their use [ 34 , 35 ]. Negative reactions may occur if therapists perceive an increase in their workload [ 36 ]—the results of the UTAUT-TAM questionnaire showed that the majority of physiotherapists replied ‘totally disagree' to the questions regarding work and productivity, suggesting that use of the Poppy robot generated more work for them, rather than relieving them. Performance expectancy has been found to be a powerful factor influencing therapist's willingness to use a technological device [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the expansion of subjective assessments could provide more comprehensive information. For instance, Gilardi et al [ 22 ] used detailed questionnaires to assess workload, quality of life, and customer experience settings related to robotic technology in pediatric neurorehabilitation. In that study, the novel robotic neurorehabilitation technique was associated significant increase in the patients’ and parents’ expectations.…”
Section: Discussionmentioning
confidence: 99%